Pertanggungjawaban Pidana terhadap Penyalahgunaan Artificial Intelligence dalam Penyebaran Konten Deepfake Melalui Media Digital - Eyrina Indah Kurniawan; Vhartsya Amanda Zaen (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The development of Artificial Intelligence (AI) technology has created new challenges in the field of cybercrime, particularly through the dissemination of deepfake content via digital media. Deepfake technology enables the manipulation of images, audio, and videos that appear authentic and are increasingly used for unlawful purposes such as digital fraud, defamation, misinformation, and identity manipulation. This study aims to analyze criminal liability for the misuse of Artificial Intelligence in the distribution of deepfake content through digital media in Indonesia. The research employs a normative juridical method with statutory, conceptual, and case approaches. Data were collected through library research using primary and secondary legal materials related to cybercrime, electronic information, and data protection. The results indicate that criminal liability for deepfake misuse can be imposed through provisions in the Criminal Code, the Electronic Information and Transactions Law, and the Personal Data Protection Law. However, the absence of specific regulations concerning AI and deepfake technology creates challenges in legal enforcement, particularly in digital evidence examination and offender identification.